Developing understanding of object fall: Going beyond inhibitory processes. (2nd May 2017) - Howe, Christine
Abstract : A study is reported where 118 participants aged between 10 years and early 20s drew the trajectories they expected objects to follow as they fell. The younger participants typically anticipated backward trajectories during fall from moving carriers while forward but non‐parabolic trajectories were relatively more frequent amongst the older participants. Both patterns suggest strong sociocultural influences, with implications for models that regard development in this area as purely the inhibition of principles established in infancy. Statement of contribution What is already known on this subject? Research with infants demonstrates an early‐established belief that dropped objects fall straight down. The erroneous expectations that pre‐schoolers hold about object fall are consistent with failure to inhibit the presumption of straight‐down fall, in contexts where it is inappropriate. What does this study add? The research replicates and extends research with older participants, which indicates errors that cannot be explained via failed inhibition of straight‐down fall. It is the first study to trace patterns of errors across late childhood, adolescence and early adulthood. A consequence of the findings is that adequate modelling in developmental psychology must consider multilayered interactions between prior representations and sociocultural experiences.